The Patterns of Distribution of the Azimuth of the Winds at the Stage of Growth the Leaves of the Birch in the Vegetation Periods 2014 and 2018 - Matveevich Mazurkin, Peter; A.I, Kudryashova (European Journal of Applied Sciences, 2019)
Formation and death of leaves in the cycle of ontogenesis are divided into the following stages: Bud growth and development of leaves, blooming dying leaves, leaf subsidence. We propose two more stages of ontogenesis – growth to the maximum and decline to the fall. The stage of growth of birch leaves hanging to the maximum width (similar to the length, area and perimeter of the leaves) of the growing season becomes a great quantum of plant behavior. This quantum with high adequacy shows that on three-time measurements of wind azimuth the distribution of the number of wind directions occurs according to the superstrong laws in 2014 and 2018. Then a three-hour quanta measurements of the azimuth of the winds make it very high to determine the adequacy of distribution of measurement directions of the wind.In 2014 had arisen three prevailing directions, growth of incidence azimuth: 45, 202.5 and 337.50. And in 2018 there were two directions of prevailing winds: 67.5 and 2700 in the city of Yoshkar-Ola. The three-hour distribution of wind directions along the azimuth at the first stage of the growing season of birch leaves from the first of may to August 20 of each year occurs according to clear laws, including wave equations with variable amplitude, changing according to the biotechnical law. For 2018, seven waves with a half-period of oscillations in the 45.1, 27.7, 23.25, 24.17, 0.23, 22.65 and 723 days. Of these, a constant period of 2 x 24.17 = 48.3 days.